2019
DOI: 10.1038/s41598-018-37709-x
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Cognitive Assessment: Speed and Accuracy of Visual Processing as a Reliable Proxy to Cognitive Performance

Abstract: Various mental disorders are accompanied by some degree of cognitive impairment. Particularly in neurodegenerative disorders, cognitive impairment is the phenotypical hallmark of the disease. Effective, accurate and timely cognitive assessment is key to early diagnosis of this family of mental disorders. Current standard-of-care techniques for cognitive assessment are primarily paper-based, and need to be administered by a healthcare professional; they are additionally language and education-dependent and typi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
51
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 36 publications
(55 citation statements)
references
References 68 publications
(59 reference statements)
3
51
1
Order By: Relevance
“…motor Comparing ICA with other reliable iPad-based cognitive tests, such as the electronic implementations of SDMT 42,43 , we would like to highlight two main differences: a) The ICA test takes advantage of an AI platform, thus the capacity to learn from big data and further fine tune its multidimensional classification boundaries when it comes to see new training cases. b) ICA did not show a learning bias in this study and a previous study 19 , as opposed to the learning bias reported for the iPad-based SDMT (i.e. PST) 42 .…”
Section: Discussioncontrasting
confidence: 57%
See 2 more Smart Citations
“…motor Comparing ICA with other reliable iPad-based cognitive tests, such as the electronic implementations of SDMT 42,43 , we would like to highlight two main differences: a) The ICA test takes advantage of an AI platform, thus the capacity to learn from big data and further fine tune its multidimensional classification boundaries when it comes to see new training cases. b) ICA did not show a learning bias in this study and a previous study 19 , as opposed to the learning bias reported for the iPad-based SDMT (i.e. PST) 42 .…”
Section: Discussioncontrasting
confidence: 57%
“…We therefore designed an iPad-based rapid visual categorization task [16][17][18] , called the Integrated Cognitive Assessment (ICA), that primarily assesses IPS in visuo-motor domains. The task is designed to give a sensitive, repeatable measure of IPS, and is additionally shown to be correlated with other cognitive domains, such as visual memory and visuospatial 19 . The test is software-based, self-administered and is shown to have little dependency on participant's language, and is not confounded by participants' different level of education 19 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The Integrated Cognitive Assessment (ICA, ) is a 5-min, self-administered, iPad-based, computerized cognitive assessment. It has been validated in patients with Mild-AD, MCI and multiple sclerosis and licensed as Software as Medical Device (SaMD) ( 51 , 52 ). The ICA is a rapid image categorization task that measures attentional speed, accuracy and attentional speed and accuracy decay over time.…”
Section: Resultsmentioning
confidence: 99%
“…It employs an artificial intelligence algorithm to improve its predictive accuracy by correlating age, gender and handedness with the composite score. The ICA does not demonstrate educational, interpretation bias or a practice effect ( 51 ) and integrates with electronic health systems. The use of the ICA aims at early detection, high-frequency monitoring of disease trajectory and response to treatment.…”
Section: Resultsmentioning
confidence: 99%